Mass Transfer Performance of Ethanol Removal by CO2 Stripping in Different Pneumatic Bioreactors - Martins, Taise B.; Almeida, Letícia P.; Cerri, Marcel O.; Badino, Alberto C. (SAGE Publications, 2020)
The hydrodynamics and mass transfer characteristics of ethanol stripping with CO2 were evaluated for a 2.0-L pneumatic bioreactor operated in bubble column (BC), concentric-tube airlift (CTA), and split-cylinder airlift (SCA) configurations, as well as for bubble columns with three different working volumes (2.0, 5.0, and 10.0 L). The results showed that an increase of the global gas hold-up (G) did not enhance ethanol removal in any of these prototypes. The volumetric ethanol removal coefficient (kLEa) values were very similar for the three models, despite the higher G obtained for the CTA configuration. The same behavior was observed for the three scales of BC prototypes, except for distinct behavior observed at the 10.0-L scale operated above 2.5 vvm. In order to predict kLEa for different scales and operational conditions, a dimensionless correlation was proposed for the Sherwood number, which provided an excellent fit to the experimental data, with few points exceeding ±10% deviation. The ethanol concentration factor (FC) values increased with decrease of the specific gas flow rates, with the highest FC value of around 6.0 (6 times the original solution concentration) obtained for the 10.0-L scale of BC. Therefore, increasing the prototype size led to an increase of Fc, resulting in greater ethanol enrichment of the gas stream leaving the equipment.
Keywords: CO2 stripping; extractive ethanol fermentation; hydrodynamics; mass transfer; pneumatic bioreactor